Analisis Peran Mediasi Pengalaman Magang dalam Transformasi Soft Skill Terhadap Perilaku Kerja Profesional Mahasiswa Vokasi - Anisa Tri Indah Sari (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
The persistent mismatch between university graduates' competencies and labor market demands highlights the critical need to develop both soft skills and practical work experience in shaping professional workplace behavior. This study aims to analyze the direct effect of soft skill students’ work behavior, assess the contribution of internship experience, and examine the mediating role of internships in the relationship between soft skills and work behavior. A quantitative approach was employed using Structural Equation Modeling (SEM). The study involved 140 people consisting of alumni and final-year students who had completed internship programs. Standardized questionnaires were used to measure soft skills, internship experience, and work behavior. The findings revealed that soft skills significantly influence both work behavior (β = 0,285; p =0,000) and internship experience (β = 0,531; p =0,000). Internship experience was also found to have a direct, significant impact on work behavior (β = 0,533; p = 0,000). Furthermore, internship experience significantly mediates the relationship between soft skills and work behavior (β = 0,283; p = 0,000). These results underscore the importance of integrating soft skill development with experiential learning opportunities such as internships within higher education curricula. The study offers practical implications for academic institutions, industries, and policymakers in designing experiential learning frameworks that enhance graduates’ readiness for the workforce.